Efficacy and Safety of Filgrastim and Its Biosimilars to Prevent Febrile Neutropenia in Cancer Patients: A Prospective Study and Meta-Analysis - Shruti Rastogi; Vivekananda Kalaiselvan; Sher Ali; Ajaz Ahmad; Sameer Ahmad Guru; Maryam Sarwat (Biology, 2021)
Background: The aim of this review and meta-analysis was to identify, assess, meta-analyze and summarize the comparative effectiveness and safety of filgrastim in head-to-head trials with placebo/no treatment, pegfilgrastim (and biosimilar filgrastim to update advances in the field. Methods: The preferred reporting items for systematic reviews and meta-analyses PRISMA statement were applied, and a random-effect model was used. Primary endpoints were the rate and duration of grade 3 or 4 neutropenia, and an incidence rate of febrile neutropenia. Secondary endpoints were time to absolute neutrophil count ANC recovery, depth of ANC nadir (lowest ANC), neutropenia-related hospitalization and other neutropenia-related complications. For filgrastim versus biosimilar filgrastim comparison, the primary efficacy endpoint was the mean difference in duration of severe neutropenia DSN. Results: A total of 56 studies were considered that included data from 13,058 cancer patients. The risk of febrile neutropenia in filgrastim versus placebo/no treatment was not statistically different. The risk ratio for febrile neutropenia was 0.58, a 42% reduction in favor of filgrastim. The most reported adverse event with FIL was bone pain. For pegfilgrastim versus filgrastim, no statistically significant difference was noted. The risk ratio was 0.90 (95% CI 0.67 to 1.12). The overall difference in duration of severe neutropenia between filgrastim and biosimilar filgrastim was not statistically significant. The risk ratio was 1.03 (95% CI 0.93 to 1.13). Conclusions: Filgrastim was effective and safe in reducing febrile neutropenia and related complications, compared to placebo/no treatment. No notable differences were found between pegfilgrastim and filgrastim in terms of efficacy and safety. However, a similar efficacy profile was observed with FIL and its biosimilars.